Lichen planus bullous treated with acitretin and PUVA therapy: a case report - Uchańska, Grażyna; Romańska-Gocka, Krystyna; Placek, Waldemar (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
Lichen planus bullous is a rare variant of lichen planus with characteristic clinical, histological and immunopathological features in which a lichenoid eruption is found in association with bullae on both involved and apparently normal skin. We present the case of patient with lichen planus bullous who couldn’t be treated with oral corticosteroids because of adverse events and who was treated successfully with combinated therapy: acitretin and PUVA therapy.